Rice resistance to stem borer. I. Evaluation through larvae feeding on stem pieces - da Silva Martins, José Francisco; Parra, José Roberto Postali; Mihsfeldt, Laila Herta (Pesquisa Agropecuaria Brasileira, 2014)
The possibility to detect the antibiosis type resistance in rice to Diatraea saccharalis was evaluated through the method of larvae feeding on stem pieces. For this the larval growth on stem pieces and on intact rice plants of resistant and susceptible varietis, to the insect, cultivated in greenhouse, was compared. The effect of feeding On stem pieces was assessed under controlled laboratory conditions, based on Insect biological parameters and the nutritional indexes approximate digestibility (AD), efficiency of lngested food conversion (ECI) and digested food (ECD). Larvae feeding on stem pieces is a feasible method for discriminating varieties for antibiosis type resistance to D. saccharalis, but not for separating the effects of the plant biophysical and biochemical factor, responsible Tor this type of resistance.
Keywords: Oryza sativa; varieties; biophysical and biochemical characteristics; Diatraea saccharalis; antibiosis; nutritional indexes.